2020
DOI: 10.3390/healthcare9010014
|View full text |Cite
|
Sign up to set email alerts
|

Increased Emergency Calls during the COVID-19 Pandemic in Saudi Arabia: A National Retrospective Study

Abstract: The coronavirus 2019 (COVID-19) pandemic has a direct and indirect effect on the different healthcare systems around the world. In this study, we aim to describe the impact on the utilization of emergency medical services (EMS) in Saudi Arabia during the COVID-19 pandemic. We studied cumulative data from emergency calls collected from the SRCA. Data were separated into three periods: before COVID-19 (1 January–29 February 2020), during COVID-19 (1 March–23 April 2020), and during the Holy Month of Ramadan (24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…12 Besides, some patients may not want to use an ambulance since COVID-19 suspected patients with symptoms such as fever and cough were transported in ambulances, and it was thought that COVID-19 was transmitted through aerosolized droplets. 1 Similar to this study, while there was a decrease in ambulance calls in Japan 1 and the United States 6 (26.1% decrease), there was an increase in Saudi Arabia 13 (22.1%-27.3% increase). It is thought that this increase was due to the strict lockdown, especially in areas with low population, and patients preferred to be transferred to the hospital via ambulance instead of using their own vehicles.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…12 Besides, some patients may not want to use an ambulance since COVID-19 suspected patients with symptoms such as fever and cough were transported in ambulances, and it was thought that COVID-19 was transmitted through aerosolized droplets. 1 Similar to this study, while there was a decrease in ambulance calls in Japan 1 and the United States 6 (26.1% decrease), there was an increase in Saudi Arabia 13 (22.1%-27.3% increase). It is thought that this increase was due to the strict lockdown, especially in areas with low population, and patients preferred to be transferred to the hospital via ambulance instead of using their own vehicles.…”
Section: Discussionsupporting
confidence: 81%
“…It is thought that this increase was due to the strict lockdown, especially in areas with low population, and patients preferred to be transferred to the hospital via ambulance instead of using their own vehicles. 13 Prehospital emergency services were established to provide rapid transport of critically injured or ill patients to the ED. In the present day, patients' frequent use of ambulances for non-emergency complaints and injuries strains the capacity of prehospital emergency health services.…”
Section: Discussionmentioning
confidence: 99%
“…Flooding today must be both appreciated and managed as multifactorial events [48][49][50][51][52]. Therefore, developing guidelines and standard operating procedures in addition to the introduction of educational interventions, such as training campaigns, and designing mobile solutions aimed to enhance the knowledge and awareness among HCWs is highly recommended [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. It is essential to make a major shift toward improvement as far as the notion of flood disaster preparedness for healthcare providers is concerned.…”
Section: Discussionmentioning
confidence: 99%
“…This was considered a panic phase because earlier outbreaks in the area had very little or close to zero infected patients, making the response to such situations different. In many countries, there is a significant increase in the use of EMS services, including phone calls, consultation, and an increasing number of operations [4], [7], [8], [9], [10], [11], [12]. However, in the areas studied, the amount of service usage dropped significantly with an average of 1-2 EMS operations per day as people were not willing to risk infection and stayed at home.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that the panic of infection among EMS personnel has increased, which is associated with increased risk of transmission to their family members [9]. In Israel, 8.51% of emergency calls were COVID-19 related, resulting in more than 4 times the typical use of emergency hotlines [10] similar to New York City [11] and Saudi Arabia [12]. A study in Japan found that the effects of this required hospitals allow for reduced delivery or increased coordination time in EMS [13].…”
Section: Introductionmentioning
confidence: 99%